Pengaruh Teknologi Informasi Pada Dunia Politik Dikalangan Masyarakat Sei Lepan Kab. Langkat - Helma Mesya Cristiani Br Siregar (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
In this digital era, information technology has created a deep transformation in the world of politics, especially among society. This research aims to identify and analyze the impacts and challenges arising from the penetration of information technology in the political sphere of society, advances in information technology, there needs to be careful steps and wise policies to overcome the challenges that arise. Increasing digital literacy among the public ensures that information technology makes a positive contribution to the political process without compromising the security and integrity of democracy. access to information evenly and quickly, enabling more active political participation and facilitating direct communication between voters and politics.